Prediction about Effect of Span-to-Depth Ratio on Shear Capacity for FRP Bar Reinforced Concrete Beams without Web Reinforcement - Danying Gao; Tao Wang; Changhui Zhang; Cong Li (Advances in Civil Engineering)
Most of the prediction models for the shear capacity of FRP bar reinforced concrete beams without web reinforcement in current codes are reported to be conservative and do not consider the effect of span-to-depth ratio. Grey relational analysis (GRA) method was used in this paper to investigate the relevance of span-to-depth ratio with the shear capacity, and the results shown that the span-to-depth ratio greatly affects the shear capacity of FRP bar reinforced concrete beams without web reinforcement. A prediction model which considers the effect of span-to-depth ratio was proposed for the shear capacity of FRP bar reinforced concrete beams without web reinforcement by regression analysis, which is more accurate and reasonable in comparison with the current models.